Who, where, when: Colorectal cancer disparities by race and ethnicity, subsite, and stage - Kristin M. Primm; Andrea Joyce Malabay; Taylor Curry; Shine Chang (Cancer Medicine, 2023)
Abstract Background There are well‐established disparities in colorectal cancer (CRC) outcomes between White and Black patients; however, assessments of CRC disparities for other racial/ethnic groups are limited. Methods The Surveillance, Epidemiology, and End Results database identified patients aged 50–74 years with CRC adenocarcinoma from 2000 to 2019. Trends in age‐adjusted incidence rates were computed by stage at diagnosis and subsite across five broad race/ethnic groups (White, Black, Asian/Pacific Islander [API], American Indian/Alaskan Native [AIAN], and Hispanic) and four API subgroups (East Asian, Southeast Asian, South Asian, and Pacific Islander) Multivariable logistic regression evaluated associations between race/ethnicity and diagnosis stage. Multivariable Cox proportional hazards models assessed differences in cause‐specific survival (CSS). Results Hispanic, AIAN, Southeast Asian, Pacific Islander, and Black patients were 3% to 28% more likely than Whites to be diagnosed with distant stage CRC, whereas East Asian and South Asians had similar or lower risk of distant stage CRC. From Cox regression analysis, Black, AIAN, and Pacific Islanders also experienced worse CSS, while East Asian and South Asian patient groups experienced better CSS. No significant differences in CSS were observed among Hispanic, Southeast Asian, and White patients. When stratified by stage, Black patients had worse CSS across all stages (early, hazard ratio (HR) = 1.38; regional, HR = 1.22; distant, HR: 1.07, p < 0.05 for all). Conclusion Despite advances in CRC screening, treatment and early detection efforts, marked racial/ethnic disparities in incidence, stage at diagnosis, and survival persist. Findings demonstrate the extent to which aggregating heterogenous populations masks significant variability in CRC outcomes within race/ethnic subgroups.